Physiology of handcycling: A current sports perspective - Stephenson, B. T.; Stone, B.; Mason, B. S.; Goosey-Tolfrey, V. L. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Handcycling is a mode of mobility, and sport format within Para-cycling, for those with a lower limb impairment. The exercise modality has been researched extensively in the rehabilitation setting. However, there is an emerging body of evidence detailing the physiological responses to handcycling in the competitive sport domain. Competitive handcyclists utilize equipment that is vastly disparate to that used for rehabilitation or recreation. Furthermore, the transferability of findings from early handcycling research to current international athletes regarding physiological profiles is severely limited. This narrative review aims to map the landscape within handcycling research and document the growing interest at the elite end of the exercise spectrum. From 58 experimental/case studies and four doctoral theses, we provide accounts of the aerobic capacity of handcyclists and the influence training status plays; present research regarding the physiological responses to handcycling performance, including tests of sprint performance; and discuss the finite information on handcyclists` training habits and efficacy of bespoke interventions. Furthermore, given the wide variety of protocols employed and participants recruited previously, we present considerations for the interpretation of existing research and recommendations for future work, all with a focus on competitive sport. The majority of studies (n = 21) reported aerobic capacity, detailing peak rates of oxygen uptake and power output, with values >3.0 L min-1 and 240 W shown in trained, male H3-H4 classification athletes. Knowledge, though, is lacking for other classifications and female athletes. Similarly, little research is available concerning sprint performance with only one from eight studies recruiting athletes with an impairment.